2018
DOI: 10.15713/ins.ijmdcr.112
|View full text |Cite
|
Sign up to set email alerts
|

Anterior maxillary distraction osteogenesis for cleft lip and palate patients - A case series

Abstract: Distraction osteogenesis (DO) has become a mainstream surgical technique for patients with jaw deformities. This case report describes the surgical orthodontic treatment of maxillary hypoplasia in two patients of 14-19 years with cleft lip and palate. They were treated with anterior maxillary DO using rigid intraoral distractor device. Distraction was started after the initial latency period with activation of 0.8 mm/day until positive overjet was gained. Cephalometric analysis was performed twice for evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The effectiveness of distraction osteogenesis (DO) in the dentoalveolar region is well-documented (Liou et al, 2000; Pai et al, 2018). Many studies have demonstrated the reduction in the size of a wide alveolar cleft through segmental DO, which allows, not only the lengthening of bone but also soft tissue expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of distraction osteogenesis (DO) in the dentoalveolar region is well-documented (Liou et al, 2000; Pai et al, 2018). Many studies have demonstrated the reduction in the size of a wide alveolar cleft through segmental DO, which allows, not only the lengthening of bone but also soft tissue expansion.…”
Section: Introductionmentioning
confidence: 99%